2010
DOI: 10.4028/www.scientific.net/msf.654-656.290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Microstructure and Mechanical Properties of Low-Carbon TRIP Steel Tube

Abstract: In this study, the effects of isothermal bainite treatment (IBT) holding time on the microstructure of transformation induced plasticity (TRIP) seamless steel tube were studied via optical microscopy, TEM and XRD. Its mechanical properties and hydroformability were evaluated by tensile test and flaring test, respectively. The results revealed that the volume fraction of retained austenite (RA) increased at first then decreased with IBT holding time for a particular set of intercritical annealing (IA) temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The presence of δ-ferrite could be attributed to the high Al content, which is a strong δ-ferrite phase stabilizer. 23,25,32 The distinction between δ-ferrite and α-ferrite might be made by classifying them as follows: α-ferrite was the product of the transformation of austenite by the ICA stage, whereas δ-ferrite originates from solidification and survives through the hot deformation. 45,46 The austenite phase was transformed into the bainitic ferrite phase following heat treatment at IBT temperature.…”
Section: Thermodynamic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of δ-ferrite could be attributed to the high Al content, which is a strong δ-ferrite phase stabilizer. 23,25,32 The distinction between δ-ferrite and α-ferrite might be made by classifying them as follows: α-ferrite was the product of the transformation of austenite by the ICA stage, whereas δ-ferrite originates from solidification and survives through the hot deformation. 45,46 The austenite phase was transformed into the bainitic ferrite phase following heat treatment at IBT temperature.…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…The reason is to delay carbide precipitation through the two-step heat-treatment process. 23,25 Yi et al 26 showed that the presence of aluminium up to 1.5 wt.% was a stabilizing element of the δ-ferrite, contributing to excellent tensile properties in all solid states. Bainite and δ-TRIP steels production might benefit from adding aluminium.…”
Section: Introductionmentioning
confidence: 99%
“…The good combination of strength and ductility of transformation induced plasticity steel results from the martensitic transformation of retained austenite during the plastic deformation process, which is called transformation induced plasticity effect [10,11]. To obtain the tubular materials with high strength as well as good plasticity, the authors have been introduced the transformation induced plasticity steel technique into tubular materials research and successfully developed the transformation induced plasticity seamless steel tube with two stage heat treatment using cold drawn steel tube [12,13]. The microstructure as well as the hydroformability have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet the requirement of strength of the complicated hollow components and reduce the difficulty of its manufacture process, the materials with high strength as well as good formability are urgently desired . On the other hand, in the material research field the transformation‐induced plasticity (TRIP) steels developed in recent years exhibit a good combination of strength and ductility . The TRIP steels offer large dynamic energy absorption and thus leads to improved crash worthiness for better passenger safety .…”
Section: Introductionmentioning
confidence: 99%